Formulation of Surfactants from Coconut Coir Containing Lignosulfonate for Surfactant - Polymer Flooding - Sagala, Farad; Manan, Muhammad A.; Nsamba, Hussein Kisiki; Galiwango, Emmanuel; Kabenge, Isa (American Journal of Science and Technology, 2016)
Interfacial tension (IFT) reduction between oil and water using surfactants has been used to recover trapped oil after the primary and secondary recovery, however petroleum based surfactants are costly. More research in required on other possible sources of surfactants that can be used to supplement the existing petroleum based surfactants. In this study, surfactant formulations mixed with Lignosulfonate which was sulfonated from local coconut coir lignin, were characterized and screened through micro emulsion phase behavior experiments as a function of Lignosulfonate, primary surfactant, and alcohol concentration. Three different formulations were evaluated for their performance in residual oil recovery when followed with a polymer flood for oil displacement experiments using sand pack model at room temperature. It was found that for the system which used decane as an oil phase, surfactant formulation consisting of 2.0% (w/v) sodium dodecyl benzenesulfonate (SDBS) and 2.0% (v/v) isopentanol was able to give high oil recovery and water solubilization ratios at 2.8% (w/v) NaCl. These oil and water solubilization ratios increased slightly when 2.0 (w/v) lignosulfonate was added into the same formulation. It was evidenced that surfactants generated from coconut coir had higher potential to recover residual oil and more promising when combined with polymers.
Keywords: Black Liquor, Phase Behavior, Lignin, Surfactant, Solubilization, Micro Emulsion